Access : introduction to travel and tourism - Mancini, Marc (Australia, 2006)
Few careers are as exciting, dynamic, and rewarding as travel. Helping people go places, enjoy themselves, and collect wonderful memories you will be making these things possible if you pursue a job in the travel industry. Why study travel? Here are five reasons: 1. Employment opportunities are excellent. By many estimates, travel- and tourism-related firms employ more people in the world than any other industry. Although the volume of travel ebbs and flows-prosperity and peace can fuel it, economic recession and terrorism can dampen it-the trend, averaged out, is always upward. 2. Advancement comes swiftly. People employed in travel and tourism quickly discover that upward mobility is the norm for this business. If you perform to the best of your ability, you will probably rise quickly on the ladder of success. 3. Your options will be plentiful. Travel is a field of great diversity. Each seg-ment of the business-lodging, air, cruises, tours, travel agent operations, and more offers its own unique and distinct personality, giving you more choice for career paths than most other businesses. 4. Travel is an immensely enjoyable industry. People in the insurance busi-ness don't get excited about insurance. People who work at office supply stores aren't likely to be passionate about office products. But travel profes-sionals? That's different. They love what they help provide and so will you. 5. It will help your own travels, too. Travel professionals often get major dis-counts on their own travels. More important, what you'll learn from this book will serve as insider information, ensuring that you will travel better and smarter.
Keywords: Cruise industry; Tourism industry; Travel industry